THE EFFECTS OF WORK FROM HOME AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE OF THE SUPERVISION TEAM AT OTORITAS JASA KEUANGAN REGIONAL OFFICE 2 WEST JAVA - Dewiyani, Wulansari; Derini, Istighfarin; Yokanigya, Desta; Destia, Gitta Triana; Bayan, Hikam Nur; Sofyandi, Rd. Herman (CENTRAL ASIA AND THE CAUCASUS, 2022)
All nations on the earth carried out arrangements to limit the spread of the Coronavirus infection. The public authority of Indonesia has mandated that all organizations in the country to execute Work From Home (WFH). If WFH does not run as expected and there is demotivation, employee performance will decrease. This paper intends to discover the effect of work from home and work motivation on the performance of employees of the supervision team at Otoritas Jasa Keuangan Regional Office 2 West Java. The research approach employed in this study is descriptive and verificative. The conveyance of online polls gathered data. The sampling method utilizes an absolute inspecting method, which is that the samples are the same as the population of 37 workers. This study demonstrates that work from home and work motivation can simultaneously positively affect employee performance. The computed F value is 22.499 when the significance level (α) is 5%, the F table value is 3.08, and the sig F is 0.000, according to the F test outcome. While working from home in part has a positive effect on employee performance, the t-test calculation shows that t count > t table, or 2.328 > 1.6909. The outcome of the t-test calculation demonstrate that work motivation has a marginally positive effect on employee performance, with t count > t table, particularly 4.754 > 1.6909.